(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Older people are more susceptible to Alzheimer's disease (AD), a neurological illness. Alzheimer's dementia now affects those aged 65 and beyond. A forgetting of earlier conversations or occurrences is the disease's first symptom. Serious memory loss and decreased ability to do daily tasks occur as the illness progresses. The damage first shows up in the part of the brain that regulates memory, but it happens years before any symptoms develop. The brain eventually becomes much smaller as the loss of neurons spreads to other regions. Mild, Moderate, and Severe are the three stages of the sickness. The early stage, also known as the intermediate stage, features emerging problems. combination of positron emission tomography and magnetic resonance imaging data for neuroimaging. This new development in medicine calls for the use of cutting-edge instruments and the processing of massive volumes of data, where artificial intelligence is applied (AI), contributes significantly to the presentation of disease-patient dynamics, which is essential for timely/optimal diagnosis, monitoring, and action. The essential components are predictive models and algorithms. in this cutting-edge industry. In this study, we provide a summary of important subjects relating to the describing the algorithms and how they are used predictive of the progression of AD and AI's application to AD biomarkers, also. Precision medicine is a new method for treating and preventing disease that integrates multimodal data with elements including lifestyle, genetics, physiology, and environmental factors. Precision medicine uses AI algorithms. In this this study provides an overview of the key ideas relating to the application of AI in AD research, with a focus on ML and DL models. Each section's subjects will be chosen based on those that were most frequently used to describe AD.